On the evolution of hyperlinking - Marques, Artur (2018)
Across time, the hyperlink object has supported different applications and studies. This is one perspective on the evolution of the hyperlinking concept, its context and related behaviors. Through a spectrum of hyperlinking applications and practices, the article contrasts the status quo with its related, broader, conceptual roots; it also bridges to some theorized and prototyped hyperlink variations, namely "stigmergic hyperlinks", to make the case that the ubiquitousness of some objects and certain usage patterns can obfuscate opportunities to (re)think them. In trying to contribute an answer to "what has the common hyperlink (such an apparently simple object) done to society, and what has society done to it?", the article identifies situations that have become so embedded in the daily routine, that it is now hard to think of hyperlinking alternatives.